The Impact of Financial Markets on The Development of Investments in Iraq - Rasha Qaband,; Anas Sajid Al-Rawi, (Eximia, 2024)
The organizational development process represents a systematic and continuous process that does not stop at a specific point. It is a continuous cycle of continuous improvement that includes drawing, developing, implementing, evaluating, improving and monitoring strategies. The organizational development process focuses on studying internal changes in the company and external changes as well and their implications for the company and its performance in order to improve communication and interaction processes. Within the company and ensuring that all employees work in consistency with the company's goals and values, developing employees, improving their capabilities, improving the products and services provided by the company to its customers, and also increasing profitability, the research aims to know the impact of organizational developments in developing investments in the financial sector in Iraq. Through statistical analysis, the results showed that the values of the regression coefficient and the beta coefficient (B) were positive. This means that organizational developments positively affect the development of investments for joint-stock companies in Iraq, that is, the greater the degree of organizational development, the greater the ability to develop investments for joint-stock companies in Iraq. The results showed that the correlation coefficient (R) was (0.629), while the results showed that the square value of the coefficient Correlation (R²), (0.396); Its interpretation means (38%) of the development of investments in the financial sector in Iraq. Based on the previous result, the hypothesis was accepted and the research recommends developing the legal environment, including the Companies Law by issuing rules for public offering and developing its mechanisms when marketing the shares of new companies or existing companies when increasing their capital. In order to attract national and foreign capital.